Penyimpangan Maksim Kesantunan Berbahasa Mahasiswa pada Dosen dalam Interaksi WhatsApp Group - Cut Nabilla Kesha; Siti Jahria Sitompul; Veni Nella Syahputri; Syafrizal Syafrizal; Desi Marlizar; Nurhaslita Sari (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
Language politeness is the key to good communication, including in communication in student WhatsApp groups. However, violations of the principle of language politeness often occur among students, especially in WhatsApp course groups. This study aims to discuss violations of the principle of language politeness among students in Indonesian language course class groups. This study uses a qualitative method with research data in the form of WhatsApp message media. The results showed that there were four violations of the maxim of wisdom, one violation of the maxim of sympathy, five violations of the maxim of generosity, and one violation of the maxim of humility. These violations occur because students think that WhatsApp groups tend to be informal and pay less attention to language politeness. The results of this study are expected to increase students' awareness of the importance of language politeness in communication, especially in WhatsApp groups.